Question answering forum system for mathematics - Siti Amirah Selamat (2017)
Tuition Centre industry in Singapore has become increasingly popular and in demand as school syllabus gets more challenging. As the number of Tuition Centre in Singapore continues to increase, parents need to spend a lot of time to review different websites that caters to their need and most importantly, find a Tuition Centre that can help improve on their children’s results. This report will discuss on the development and implementation of the project, “experTuition”, a Tuition Centre System. It is a web-application that lists Tuition Centre that are available in Singapore including its different branches and displays the class or lesson that they will be conducting. It is implemented to ease parents in finding the right Tuition Centre that meets their requirements. Hence, the system must be user-friendly and allows user to search for Tuition Centre easily. Thus, Django, MySQL, JavaScript and Bootstrap 3 were used to develop “experTuition”. ExperTuition is developed to list Tuition Centre in Singapore where users can filter based on education level, subject and/or location. There is also an administration side for the Tuition Centre administrator to create different branch and lessons to allow the parents to book the lesson instantly through “experTuition”.